Independence of the Islamic Students Association Responding to Indonesian Politics, Perceptions of Online Media - Suhadak, Totok; Utama, Abdul Alimun (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This article discusses the HMI issue, the main issue discussing the independence of the Islamic Student Association organization towards national politics, fully using historical research methods (History Research) with historical methods starting from the Heuristic, Criticism, Interpretation and Historiography stages. This article aims to find out about the HMI organization in the Indonesian political arena regarding the perception of online media. The data analysis technique in this research places more emphasis on the process of searching for data from online media which is carried out using internet studies. Based on the research results, it shows that the HMI Organization in its development has always been independent in the nation's political arena, even if there are cadres who take part in politics, it is the personal right of each individual.